APPLICATION OF STUDENTS’ WORKSHEET WITH PROJECT BASED LEARNING MODEL: INNOVATION STRATEGIES TO TRAIN STUDENTS' COLLABORATION SKILLS - Rahman, Rini Yunita; Nurhayati, Dwi Siti; Hidayatussaadah, Rulis; Rahmawati, Laifa; Nurrohman, Sabar; Winarto, Winarto (Universitas Bhinneka PGRI, 2026)
The study aims to describe the results of the implementation of Students’ Worksheets with the Project-Based Learning (PjBL) model in training students' collaboration skills. The research uses the Pre-Experiment method with a One-Group Pretest-Posttest design. The population consisted of 224 students from 7 study groups, which were then selected 1 class with a total of 30 students from class VII B SMPN 1 Sleman. The instrument used was in the form of a collaboration questionnaire and the results were analyzed statistically descriptively. The results showed that the average pretest score was 35.13 and the posttest was 59.62. This increase was confirmed through an N-Gain score of 0.36 which is classified as a medium category, These findings show that the implementation of LKPD with the PjBL model is quite effective in training students' collaboration skills, as well as making a positive contribution to the development of their collaborative abilities in the learning process.